2010
DOI: 10.1097/fjc.0b013e3181e74a14
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolic Phenotype of the Cardiomyocyte During Development, Differentiation, and Postnatal Maturation

Abstract: Dramatic maturational changes occur in cardiac energy metabolism during cardiac development, differentiation, and postnatal growth. These changes in energy metabolism have important impacts on the ability of the cardiomyocyte to proliferate during early cardiac development, as well as when cardiomyocytes terminally differentiate during later development. During early cardiac development, glycolysis is a major source of energy for proliferating cardiomyocytes. As cardiomyocytes mature and become terminally diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
516
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(536 citation statements)
references
References 164 publications
(213 reference statements)
20
516
0
Order By: Relevance
“…We next determined the effect of an adult-like lipogenic milieu on neonatal cardiomyocytes by treatment with a 3F protocol consisting of insulin, 3-isobutylmethylxanthine, and dexamethasone for 10 days (23). In control cardiomyocytes, the 3F protocol switched the embryo-like metabolism dominated by glycolysis (25) to an adult-like metabolism, which was characterized by an increased baseline OCR (Fig. 1E), and more fatty acid ␤-oxidation (Fig.…”
Section: Fasn Transgenic Cardiomyocytes Developed a Dysfunctionalmentioning
confidence: 99%
“…We next determined the effect of an adult-like lipogenic milieu on neonatal cardiomyocytes by treatment with a 3F protocol consisting of insulin, 3-isobutylmethylxanthine, and dexamethasone for 10 days (23). In control cardiomyocytes, the 3F protocol switched the embryo-like metabolism dominated by glycolysis (25) to an adult-like metabolism, which was characterized by an increased baseline OCR (Fig. 1E), and more fatty acid ␤-oxidation (Fig.…”
Section: Fasn Transgenic Cardiomyocytes Developed a Dysfunctionalmentioning
confidence: 99%
“…This is contrary to observations in intact hearts subjected to hypoxia, which very quickly become depleted of ATP and PCr. Adult cardiomyocytes depend on β ‐oxidation of fatty acids to generate ATP, whereas the neonate cardiomyocytes have not developed β ‐oxidation capabilities and use glycolysis as the main ATP generation pathway (Lopaschuk and Jaswal 2010). RNCMs are thus capable of maintaining constant ATP levels even when subjected to prolonged hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Thus determining the rate of oxygen respiration would provide an ideal measure of oxidative phosphorylation in differentiated H9c2 cells. It should be noted that this variable was only investigated in cells differentiated for 6 days and no fatty acids were included as the researchers merely aimed to establish if a change in oxygen consumption was evident following differentiation.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
“…(20) Lopashuk, et al (2010) identified that a switch from glycolysis to oxidative phosphorylation is a fundamental characteristic of differentiated cardiac cells, since cardiomyotubes prefer fatty acids to glucose as a source of fuel. (21) It could be argued that when differentiated, the H9c2 cells would offer a more closely matched representation of adult cardiomyocytes than when undifferentiated. Menard, et al (1999) stated that the H9c2 cells are easy to manipulate, and when differentiated, provide a suitable cardiac cellular model with a maintained cardiac phenotype for a range of investigations commonly challenging to perform on primary cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%